Cut in half : the hidden world inside everyday objects. - Warren, Mike, ....-; Woodward, Jonothan, ....- (San Francisco : Chronicle Books, 2018)
What exactly is inside a laptop, a golf ball, a vacuum cleaner, or a novelty singing fish toy? The insides of these and dozens of other objects are revealed in this photographic exploration of the stuff all around us, exposed and explained. With the help of a high-pressure waterjet cutter able to slice through 4 inches of steel plate, designer and fabricator Mike Warren (creator of the popular Cut in Half YouTube channel) cuts into everything from boom boxes to boxing gloves, oil filters to seashells, describing and demystifying the inner workings and materials of each. With a cleverly die-cut case and gorgeously detailed photography, Cut in Half is a fascinating and accessible popular science look at the extraordinary in the everyday
Keywords: toegepaste mechanica